Review of Microgrids to Enhance Power System Resilience - Jian-Hua He; Jhih-Hao Lin (Engineering Proceedings)
As the frequency of extreme events keeps increasing, large-scale power system interruption is also increasing. Natural disasters cause more extensive damage than typical power outages or failures, and the system demands a longer recovery period. Accordingly, it is crucial and urgent for the power system to have resilience in addition to possessing strong robustness and reliability. For the power system resilience, time is a critical factor. The microgrid (MG) can be connected to the main grid or operate independently to significantly improve the flexibility of the system with great potential in enhancing the power system resilience. We summarize the important concepts of power system resilience and MGs to improve power system resilience. Useful references are provided in this article for power-related practitioners regarding efficient design schemes to improve the application of MGs in enhancing resilience.